Pelatihan TOEFL untuk Peningkatan Kemampuan Bahasa Asing Bagi Dosen Universitas Hein Namotemo (UNHENA) - Magfirah, Sulmi; Adam, Sutisno (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Test of English as a Foreign Language (TOEFL) is a standardized test to measure the English Language ability of non-native speakers taken by students applying to universities. The ability to understand foreign languages, including the importance of studying TOEFL, is one of the supporting factors for academics in continuing their studies to a higher level, including for lecturers of Hein Namotemo University who are required to continue their studies to Master and Doctoral degrees. However, the problems are the insufficient TOEFL score hindered the scholarship provider's requirements. Departing from these problems, the team sought a solution by conducting TOEFL score improvement training which would then be utilized according to the academic needs. Therefore, this community service training aims to equip educators and staff to improve their foreign language skills through TOEFL training. Thus, the results of the activities carried out had a positive impact on the Lecturers and Staff at UNHENA, as evidenced by the enthusiasm of the participants who took an active role during the activity and asked Unkhair team to continue the program, especially foreign language training, This is in accordance with the purpose of Community Service, which is beneficial to the society.